Cromoblastomicose no Maranhão: uma abordagem microbiológica, ambiental e molecular - Sirlei Garcia Marques (2010)
The chromoblastomycosis (CBM) is a chronic fungal infection of skin and subcutaneous tissue caused by several melanized fungi of Chaetotrhyales order. Fonsecaea pedrosoi is the major causative agent of the disease. This study aimed to evaluate the clinical andepidemiological aspects of patients with CBM and phenotypic and genotypic characterization of the agents isolated from clinical and environmental samples from an Amazon region of Maranhão state, Brazil. We evaluated 41 patients from the state of Maranhão with a clinical diagnosis of CBM, from September 2006 to October 2009. Among the environmental samples (236), were isolated 64 dematiaceous fungi. F. pedrosoi was the predominant agent of clinical specimens (95.2%), followed by Phialophora verrucosa (2.4%) and Rhinocladiella aquaspersa (2.4%). Among the environmental isolates, Exophiala sp. was the most prevalent (45.3%). In this study the patients aremainly male rural workers, illiterate, with an average age of 58 ± 10.6 years and time course of disease ranged from 8.8 ± 7.8 years. The lower limbs were most affected; the moderate and vegetating plaque-type lesions are the most prevalent. The lesional polymorphism was observed in most individuals. The presence of secondary bacterialinfection was found in 92.7% of individuals, and Staphylococcus aureus was the most prevalent bacteria, while the mixed bacterial infection was associated with severity injury (p = 0.01). The antifungal susceptibility testing was performed by the microdilution technique of CLSI (Clinical and Laboratory Standards Institute) and the profile of susceptibility to antibacterial agents by agar diffusion method. Itraconazole and terbinafine were the most active drugs against the fungi evaluated. The MIC values of itraconazole and voriconazole obtained against the environmental samples were the lowest among the tested antifungals. Twenty seven (100%) of Gram-positive aerobes were sensitive tovancomycin and linezolid. The isolates of S. aureus and S. aureus negative coagulase (SCN) showed a high sensitivity to ampicillin/sulbactam, cefazolin, clindamycin, gentamicin, oxacillin and rifampin. These agents showed a higher rate of resistance toerythromycin, penicillin and trimethoprim + trimpetoprim. Genetic characterization of the isolates from 40 clinical samples and 16 of environmental source was carried out by RAPD using primers specific to F. pedrosoi. Analysis of the dendrogram obtained and the similarity between the genetic profiles generated showed the formation of four distinct groups, where the most samples of clinical origin were grouped in group II and those of environmental origin in group IV. Sequencing of five biopsies of patients with CBM, five environmental samples and nine strains of fungi isolated from lesions of patients with CBM identified as F. pedrosoi showed high nucleotide similarities ranging from 92 to100% for F. pedrosoi. The determination of antimicrobial susceptibility of bacteria causing secondary infection in the lesions of CBM could be of great importance for the implementation of more effective therapy for the disease. Direct DNA extraction of fungi that cause the CBM from tissue biopsy could be important for improving and speeding the diagnosis and control of the disease.